Sex-workers in Bangladesh, livelihood, at what price? - Tahmina, Q. A.; Moral, Shishir (Dhaka : Society for Environment and Human Development,(SEHD), 2004)
Contributed articles.
Includes bibliographical references (p. [273]-276).
Keywords: Prostitutes -- Bangladesh